Nurses' knowledge and Compliance with Universal Precautions in Hilla Teaching Hospitals - Talib M. Kudhair (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To assess nurses' knowledge and compliance with universal precautions and their relationship withsome sociodemographic characteristics.Methodology: A convenience sample of (loo) nurses (males and females) were working in Hilla Teachinga:SPp'e::%Moefrj#if:;.'¥stani:,ab#'e°ne#teoTj#,d2Poa;:£a#:SuE°Sfifas[e)syejrnet:::ec:d;yDau:jrger:C:;`nesc;eudctfe°drquestiormaire based on the universal precautions (UPs) guidelines recommended by the centres for diseasescontrol and prevention (CDC) that contains (22) items. Reliability and validity of the tool were deteminedthrough a pilot study and a panel of 4 experts. Descriptive and inferential statistical approaches were used fordata analysis.Results: The study indicated that nurses' knowledge and compliance with UPs were unacceptable and there is asignificant relationship between nurses' knowledge and compliance with UPs and some sociodemographiccharacteristics.Recommendations: The study recommended that an education program can be designed, constructed andimplemented to the nurses related to UPs as well as further and nationwide studies can be conducted on a largesample size of nurses.